Exogenous Aspergillus aculeatus Enhances Drought and Heat Tolerance of Perennial Ryegrass - Li, Xiaoning; Zhao, Chuncheng; Zhang, Ting; Wang, Guangyang; Amombo, Erick; Xie, Yan; Fu, Jinmin (Frontiers in Microbiology, 2021)
Perennial ryegrass (Lolium perenne) is a cool-season grass whose growth and development are limited by drought and high temperature. Aspergillus aculeatus has been reported to promote plant growth and counteract the adverse effects of abiotic stresses. The objective of this study was to assess A. aculeatus-induced response mechanisms to drought and heat resistance in perennial ryegrass. We evaluated the physiological and biochemical markers of drought and heat stress based on the growth rate, photosynthesis, antioxidant enzymes activity, lipid peroxidation, and hormone homeostasis. We found out that under drought and heat stress, A. aculeatus-inoculated leaves exhibited higher ABA and lower SA contents than non-inoculated regimes. In addition, under drought and heat stress, the fungus enhanced the photosynthetic performance, decreased the antioxidase activities, and mitigated membrane lipid peroxidation compared to non-inoculated regime. Furthermore, under drought stress, A. aculeatus induced a dramatic upregulation of sHSP17.8 and DREB1A and a downregulation of POD47, Cu/ZnSOD and FeSOD genes. In addition, under heat stress, A. aculeatus-inoculated plants exhibited a higher expression level of HSP26.7a, sHSP17.8 and DREB1A while a lower expression level of POD47 and FeSOD than non-inoculated ones. Our results provide an evidence of the protective role of A. aculeatus in perennial ryegrass response to drought and heat stresses.